Comparisons of tympanic membrane, abdominal skin, axillary, and rectal temperature measurements in term and preterm neonates - Veena Jirapaet (2018)
Quasi-experimental research was conducted to investigate the optimum placement time and normative values of temperature measurements from the tympanic membrane, abdominal skin, axilla, and rectum of neonates at a newborn nursery of a university medical center in Thailand. A convenience sample of 52 growing preterm and 57 healthy term neonates was enrolled. Simultaneous temperature measurements were made at the four sites. Temperatures were recorded when they had remained unchanged for 2 min. The axillary temperature was as accurate as the rectal temperature measured with a glass thermometer if the placement times were optimal. The mean placement times in preterm and term neonates were 2.8 and 3.4 min for the rectum, 5.4 and 7.9 min for axilla, and 4.0 and 6.1 min for abdominal skin, respectively. The rectal temperature equalled the abdominal skin temperature plus 0.3°C for preterm and plus 0.2°C for term neonates. However, temperatures obtained with an infrared tympanic thermometer in the rectal-equivalent mode did not give an accurate reading and are not recommended as a substitute for rectal temperatures in neonates.